Vision Assessment Theoretische Reflexionen zur Erforschung soziotechnischer Zukünfte - Frey, Philipp (KIT Scientific Publishing, 2022)
Visions of the future play an increasing role in all spheres of society, in science and policy making as well as in civil society and mass media. Since 2012, researchers at the Institute for Technology Assessment and Systems Analysis have been developing "Vision Assessment" as an approach to investigate the societal effects of such visions. This anthology presents the theoretical foundations of their research.